Recent advances in culture-based gut microbiome research - Thomas C.A. Hitch; Afrizal Afrizal; Thomas Riedel; Antonios Kioukis; Dirk Haller; Ilias Lagkouvardos; Jörg Overmann; Thomas Clavel (Elsevier, 2021)
Gut microbes affect the physiology of their hosts. Studying their diversity and functions is thus of utmost importance as it will open new avenues towards the discovery of new biomolecules and the treatment of diseases. Gut microbiome research is currently boosted by the unification of metagenomics, which has dominated the field in the last two decades, and cultivation, which is experiencing a renaissance. Each of these approaches has advantages and drawbacks that can be overcome if used synergistically. In this brief article, we summarize recent literature and own studies on the cultivation of gut microbes, provide a succinct status quo of cultured fractions and collections of isolates, and give short opinions on challenges and next steps to take.